Subclinical thyroid dysfunction and cardiovascular diseases: 2016 update. (27th February 2017) - Floriani, Carmen; Gencer, Baris; Collet, Tinh-Hai; Rodondi, Nicolas
Abstract: Subclinical thyroid dysfunction comprises subclinical hypothyroidism (SHypo), defined as elevated thyroid-stimulating hormone (TSH) by normal free thyroxine (FT4), and subclinical hyperthyroidism (SHyper) with decreased or undetectable TSH and normal FT4. Up to 10% of the elderly have SHypo, which is usually asymptomatic. Individual participant data (IPD) analyses of prospective cohort studies from the international Thyroid Studies Collaboration show that SHypo is associated with increased coronary heart disease (CHD) mortality [hazard ratio (HR) 1, 58 for TSH ≥ 10 mIU/L, 95% CI 1.10–2.27), as well as increased risk of stroke, and heart failure (HF) for both higher and lower TSH. Small studies found that SHypo affects carotid intima media thickness (CIMT), diastolic function, peripheral vascular resistance, endothelial function, and lipid profile. SHyper is associated with increased risk of atrial fibrillation (AF) (HR 1.68, 95% CI 1.16–2.43) and CHD events (HR 1.21, 95% CI 0.99–1.46). The TSH threshold for initiating treatment is unclear. In the absence of large randomized controlled trials, the best evidence suggests SHypo therapy should be started at TSH ≥ 10 mIU/L, and SHyper therapy at TSH < 0.1 mIU/L. Recommendations on screening are discordant, but most guidelines advocate that thyroid function should be checked in those at risk for hypothyroidism, those over 60, and those with known CHD and HF. This review updates current evidence on the association between thyroid dysfunction and cardiovascular disease, as well as on screening and treatment of subclinical thyroid dysfunction.